Self-Harm Intervention: Family Therapy (SHIFT), a study protocol for a randomised controlled trial of family therapy versus treatment as usual for young people seen after a second or subsequent episode of self-harm . Issue 1 (December 2015) - Wright-Hughes, Alexandra; Graham, Elizabeth; Farrin, Amanda; Collinson, Michelle; Boston, Paula; Eisler, Ivan; Fortune, Sarah; Green, Jonathan; House, Allan; Owens, David; Simic, Mima; Tubeuf, Sandy; et al.
Abstract Background Self-harm is common in the community with a lifetime prevalence of 13 %. It is associated with an elevated risk of overall mortality and suicide. People who harm themselves are high users of public services. Estimates of the 1-year risk of repetition vary between 5 and 15 % per year. Currently, limited evidence exists on the effectiveness of clinical interventions for young people who engage in self-harm. Recent reviews have failed to demonstrate any effect on reducing repetition of self-harm among adolescents receiving a range of treatment approaches. Family factors are particularly important risk factors associated with fatal and non-fatal self-harm among children and adolescents. Family therapy focuses on the relationships, roles and communication patterns between family members, but there have been relatively few studies of specifically family-focused interventions with this population. The Self-Harm Intervention: Family Therapy (SHIFT) Trial was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme (grant no. 07/33/01) following a commissioned call for this research. Methods/Design SHIFT is a pragmatic, phase III, multicentre, individually randomised, controlled trial comparing Family Therapy (FT) with treatment as usual (TAU) for adolescents aged 11 to 17 who have engaged in at least two episodes of self-harm. Both therapeutic interventions were delivered within the National Health Service (NHS) Child and Adolescent Mental Health Services (CAMHS) in England. Participants and therapists were, of necessity, aware of treatment allocation, but the researchers were blind to the allocations to allow unbiased collection of follow-up data. Primary outcome data (repetition of self-harm leading to hospital attendance 18 months post-randomisation) were collected from the Health and Social Care Information Centre (HSCIC), augmented by directed searches of medical records at Acute Trusts. Secondary outcome data (including suicidal intent, depression, hopelessness and health economics) were collected at 12 and 18 months post-randomisation via researcher-participant interviews and by post at 3 and 6 months. Discussion SHIFT will provide a well-powered evaluation of the clinical and cost effectiveness of Family Therapy for young people who have self-harmed on more than one occasion. The study will be reported in 2016, and the results will inform clinical practice thereafter. Trial registration ISRCTN59793150 . 26 January 2009.